Review of array antenna and its application based on electromagnetic surface - Songlin ZHOU; Junwen TANG; Luohao LIU; You WU; Changhao LIU; Yifei JIN; Fan YANG; Shenheng XU; Maokun LI (Tongxin xuebao)
Array antennas based on electromagnetic surface is a frontier in the field of electromagnetic, based on this, the development, research status and applications of electromagnetic surface array antennas were summarized.First, the early development of electromagnetic surface was introduced.Then, the current research status of electromagnetic surface array was summarized, including reconfigurable design, broadband, terahertz, multi-polarization, etc.Subsequently, some applications in communication, radar and electromagnetic environment regulation were presented.Finally, the possible research directions of electromagnetic surface array antenna were expected.